Efficacy of Leases and Tenancies in Nigeria - Mike Takim Otu; Joseph Edet; Emmanuel Bassey Asuquo (dialektika kontemporer, 2023)
The objective of this study is to examine the effectiveness of leases and tenancies in Nigeria while analysing the associated challenges and potential avenues for enhancing the lessor-lessee and landlord-tenant relationships. Both leases and tenancies are forms of land ownership. While the phrases “leases” and “tenancies” are often used interchangeably, it is important to note that they do not strictly adhere to the same definition. Leases typically include a greater level of interest, while tenancies tend to have a shorter length. The legal meaning of a lease agreement is that the lessor maintains ownership, while in an assignment, the seller only conveys possession or occupancy. It is important to note that the Land Use Act did not eliminate the notion of leases and tenancies. Despite the presence of the Land Use Act (LUA), tenancy agreements continue to be regularly established in Nigeria since the legislation does not prohibit the conveyance of land or its subsequent development. It is important to underscore that, in addition to the Western and Midwestern states, which were the first adopters of the Landlord and Tenant Laws, primarily influenced by the English Landlord and Tenant Act of 1927, other states in Nigeria have since passed their own Landlord and Tenant Laws. This study posits that the performance and operation of leases and tenancies in Nigeria are suboptimal. The changes outlined in this paper have the potential to significantly mitigate these difficulties and provide opportunities for more efficient, effective, and enhanced leasing and tenancy practices in Nigeria. This article posits the need to enhance the institutional and legal frameworks governing leases and tenancies in Nigeria in order to provide adequate protection for both lessors and lessees.